2013
DOI: 10.1242/jcs.117705
|View full text |Cite
|
Sign up to set email alerts
|

Lipid phosphate phosphatase 3 participates in transport carrier formation and protein trafficking in the early secretory pathway

Abstract: SummaryThe inhibition of phosphatidic acid phosphatase (PAP) activity by propanolol indicates that diacylglycerol (DAG) is required for the formation of transport carriers at the Golgi and for retrograde trafficking to the ER. Here we report that the PAP2 family member lipid phosphate phosphatase 3 (LPP3, also known as PAP2b) localizes in compartments of the secretory pathway from ER export sites to the Golgi complex. The depletion of human LPP3: (i) reduces the number of tubules generated from the ER-Golgi in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 78 publications
(89 reference statements)
3
34
0
Order By: Relevance
“…Overexpression of LPP3 in Swiss 3T3 and HEK293 cells increases the conversion of PA to DG ( 90 ). LPP3 depletion decreases the levels of de novo synthesized DG and the Golgi-associated DG content, which impairs protein traffi cking in the early secretory pathway ( 91 ). Furthermore, LPP2 and LPP3 decrease cell survival by regulating the intracellular levels of PA ( 92 ).…”
Section: The Role Of Lpps In Pathologymentioning
confidence: 99%
“…Overexpression of LPP3 in Swiss 3T3 and HEK293 cells increases the conversion of PA to DG ( 90 ). LPP3 depletion decreases the levels of de novo synthesized DG and the Golgi-associated DG content, which impairs protein traffi cking in the early secretory pathway ( 91 ). Furthermore, LPP2 and LPP3 decrease cell survival by regulating the intracellular levels of PA ( 92 ).…”
Section: The Role Of Lpps In Pathologymentioning
confidence: 99%
“…Immunofluorescence Microscopy-HeLa cells were fixed and processed as described previously (53). Working dilutions of antibodies were as follows: anti-GM130 (1:1000); anti-Golgin97 (1:300); anti-TGN46 (1:500).…”
Section: ϫ05mentioning
confidence: 99%
“…These include pathways mediated by the Raf and mTOR protein kinases and conventional protein kinases C ( 13 , 14 ). Evidence that LPP3 has an intracellular role as a regulator of vesicular transport between the endoplasmic reticulum and Golgi apparatus has also been reported ( 15 ). It is also important to note that not all studies of the effects of LPP overexpression have revealed phenotypes in cell and animals that can be explained simply by attenuation of LPA signaling ( 16 ).…”
mentioning
confidence: 98%